Perceived Psychological Well-Being Among University Students: A Comparative Study by Gender - Perla Jannet Jurado García; Fernando Mondaca Fernández; Leticia Irene Franco Gallegos; Edgar Francisco Ordoñez Bencomo; Carolina Jiménez Lira; Susana Ivonne Aguirre Vásquez (European Scientific Journal, ESJ, 2019)
The aim of the present study was to compare the profiles of well-being between men and women Mexican university students. A total sample of 708 participants, 374 women and 334 men, aged 18-26 years participated in this study. A quantitative approach with a descriptive and transversal survey design was used. All the participants completed the Spanish version of the Psychological Well-Being Scales. The results of the one-way multivariate analysis of variance, followed by the one-way univariate analyses of variance, showed that compared with the women, the men obtained higher scores on the subscales self-acceptance, positive relationships, autonomy, environmental mastery, purpose in life and personal growth. Because of the differences between men and women in their perception of well-being found, these findings suggest that in order to design any intervention for improving the perceived well-being of the students, the variable gender should be taken into account.